Грибко О.В. Основні підходи до визначення поняття “якість освіти” - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The issue is devoted to the de nition of “quality” from the point of view of philosophy, economics, management. The essence of the concept of “education quality” is outlined, a number of factors thatinuence on the quality of education are done